KETAHANAN 20 JENIS KAYU TERHADAP SERANGAN RAYAP TANAH (Coptotermes curvignathus Holmgren) dan RAYAP KAYU KERING (Cryptotermes cynocephalus Light) - Jasni; Sri Rulliaty (BRIN Publishing, 2015)
This study aims to determine the resistance of 20 wood species against subterranean termites (Coptotermes curvignathus Holmgren) and dry wood termites (Cryptotermes cynocephalus Light). The test method of subterranean and dry wood termites refers to the SNI 01-7207-2006. Parameters observed for determining resistance class to subterranean and dry wood termites are the percentage of wood weight loss and the survival percentage of termites. Besides that, a subjective observation an severity of subterranean and dry wood termites attacks were also conducted. Results show that the resistance of 20 wood species against subterranean termites are as follow: class II (3 wood species), class III (2 wood species), class IV (13 wood species) and class V (2 wood species). The resistance to dry wood termites of the 20 wood studied species can be grouped as follow: class I (4 wood species), class II (5 wood species), class III (8 wood species) and classIV (3 wood species).